The Effect of Parathion on Red Blood Cell Acetylcholinesterase in the Wistar Rat - Naofumi Bunya; Keigo Sawamoto; Hanif Benoit; Steven B. Bird (Journal of Toxicology)
Organophosphorus (OP) pesticide poisoning is a significant problem worldwide. Research into new antidotes for these acetylcholinesterase inhibitors, and even optimal doses for current therapies, is hindered by a lack of standardized animal models. In this study, we sought to characterize the effects of the OP pesticide parathion on acetylcholinesterase in a Wistar rat model that included comprehensive medical care. Methods. Male Wistar rats were intubated and mechanically ventilated and then poisoned with between 20 mg/kg and 60 mg/kg of intravenous parathion. Upon developing signs of poisoning, the rats were treated with standard critical care, including atropine, pralidoxime chloride, and midazolam, for up to 48 hours. Acetylcholinesterase activity was determined serially for up to 8 days after poisoning. Results. At all doses of parathion, maximal depression of acetylcholinesterase occurred at 3 hours after poisoning. Acetylcholinesterase recovered to nearly 50% of baseline activity by day 4 in the 20 mg/kg cohort and by day 5 in the 40 and 60 mg/kg cohorts. At day 8, most rats’ acetylcholinesterase had recovered to roughly 70% of baseline. These data should be useful in developing rodent models of acute OP pesticide poisoning.